Pengembangan Aplikasi Pengukuran TKT Online - Huda M Elmatsani (Jurnal Rekayasa Elektrika, 2017)
To enhance national competitiveness, the Ministry of Research, Technology and Higher Education obliges researchers to measure the Technology Readiness Level (TRL) to the technology they develop. The goal is to know the status and maturity of the researches in Indonesia so that technology development becomes more focused and goal-directed. To realize this, it is necessary to use measurement tools that researchers throughout Indonesia can use. This paper discusses the development of the TRL Online Measurement Application which can be accessed and used by researchers. The results show that the application developed can meet the needs of the Ministry and can be used by researchers in conducting TRL measurements.